2003
DOI: 10.1080/0141861031000111129
|View full text |Cite
|
Sign up to set email alerts
|

Strongly anisotropic s-wave gaps in exotic superconductors

Abstract: The exotic superconductors, defined as those which follow the phenomenological trend of Uemura (T c approximately µ l L -2 ), presently constitute the most broad and general class of superconductors which can reasonably be considered "similar to the high-T c cuprates". It is therefore of much interest to determine the forms of their pairing gap functions. We examine evidence for the gap forms in non-cuprate exotics, and demonstrate some general features. The cubic materials often have highly anisotropic gaps. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 281 publications
(396 reference statements)
1
23
0
Order By: Relevance
“…We should recall that in extreme type-II superconductors with highly diluted superfluid density the presence of some anisotropy in the gap function is quite common. 32 Finally, it is worth noticing that our λ ab (0) value is comparable with those found in alkali-metal organicsolvent intercalated iron-selenide superconductors. 33 By considering an interlayer distance equal to the c-axis parameter 4 we can estimate a 2D superfluid density d/λ 2 ab (0) ∼ 0.0056 µm −1 .…”
mentioning
confidence: 55%
“…We should recall that in extreme type-II superconductors with highly diluted superfluid density the presence of some anisotropy in the gap function is quite common. 32 Finally, it is worth noticing that our λ ab (0) value is comparable with those found in alkali-metal organicsolvent intercalated iron-selenide superconductors. 33 By considering an interlayer distance equal to the c-axis parameter 4 we can estimate a 2D superfluid density d/λ 2 ab (0) ∼ 0.0056 µm −1 .…”
mentioning
confidence: 55%
“…Patterns for both order parameters differ substantially. Since T c0 > T d0 in the whole relevant interval Equation (19), the critical temperature T c = T c0 is not affected by the dielectric gapping. The parameter ∆(0) rapidly decreases with σ 0 , since the upper part of the ∆(T )-dependence in Figure 17(b) is effectively cut away in comparison with typical theoretical or observed BCS-like curves, so that a conventional increase of ∆(T ) at low T is arrested for this set of problem parameters.…”
Section: Complete Fs Dielectrizationmentioning
confidence: 99%
“…On the other hand, regarded as phonon-mediated superconductors, 3-7 borocarbide YNi 2 B 2 C and LuNi 2 B 2 C have turned out to have large SC gap anisotropy with nodes. [8][9][10][11][12] Since such an extremely large gap anisotropy cannot be obtained from a simple s-wave paring wave function that is assumed for a phonon-mediated superconductor, it is surprising and a challenge of condensed matter physics 13 as to what kind of interactions play an essential role and how such an extremely large anisotropy is produced.For understanding the origin of the large SC gap anisotropy, it has been considered essential to determine the direction and type of nodal structure and to study its relation to nesting vector 14,15 reported in borocarbides. However, results are controversial: the magnetic field orientation dependence of thermal conductivity, 16 ultrasonic attenuation, 17 and scanning tunneling microscopy/spectroscopy in the vortex state 18 have reported point nodes located along ͓100͔ and ͓010͔ directions while field-angle-dependent heat capacity suggested a linelike nodal structure.…”
mentioning
confidence: 99%
“…On the other hand, regarded as phonon-mediated superconductors, [3][4][5][6][7] borocarbide YNi 2 B 2 C and LuNi 2 B 2 C have turned out to have large SC gap anisotropy with nodes. [8][9][10][11][12] Since such an extremely large gap anisotropy cannot be obtained from a simple s-wave paring wave function that is assumed for a phonon-mediated superconductor, it is surprising and a challenge of condensed matter physics 13 as to what kind of interactions play an essential role and how such an extremely large anisotropy is produced.…”
mentioning
confidence: 99%